1977
DOI: 10.1073/pnas.74.6.2564
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a type C RNA virus from an established human histiocytic lymphoma cell line.

Abstract: A type C RNA virus has been detected in the culture fluids of the SU-DHL-1 human histiocytic lymphoma cell line previously established in this laboratory. In electron micrographs, the virus closely resembled other typical mammalian type C RNA tumor viruses in size and morphology. Viral RNA-dependent DNA polymerase activity has been demonstrated in particles (densities of 1.15 and 1.22 g/ml) in the microsomal cytoplasmic fraction and in pellets of culture fluids. The enzyme is partially inhibited by antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 29 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…Most of these isolates are very closely related to previously isolated type C primate viruses (5)(6)(7), making interpretations of their origin difficult. The detection of retrovirus particles from some novel cell lines from patients with diffuse histocytic lymphoma has been recently described (8) and, although the DNA polymerase from these particles is also related to the reverse transcriptase (RT; RNA-dependent DNA nucleotidyltransferase) of type C primate viruses [simian sarcoma virus-gibbon ape leukemia virus (SSV-GALV) group], peptide maps of the purified DNA polymerases show significant differences between them (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these isolates are very closely related to previously isolated type C primate viruses (5)(6)(7), making interpretations of their origin difficult. The detection of retrovirus particles from some novel cell lines from patients with diffuse histocytic lymphoma has been recently described (8) and, although the DNA polymerase from these particles is also related to the reverse transcriptase (RT; RNA-dependent DNA nucleotidyltransferase) of type C primate viruses [simian sarcoma virus-gibbon ape leukemia virus (SSV-GALV) group], peptide maps of the purified DNA polymerases show significant differences between them (10,11).…”
mentioning
confidence: 99%
“…Although some studies have suggested the presence of retrovirus information in some human tissues (3,4), the detection and isolation of complete, well-defined particles from humans has proven exceedingly difficult. The recent development of continuously growing cell lines from patients with various neoplastic diseases, and in some cases from normal tissues, has led to reports of retroviruses in some of them (5)(6)(7)(8)(9). Most of these isolates are very closely related to previously isolated type C primate viruses (5)(6)(7), making interpretations of their origin difficult.…”
mentioning
confidence: 99%
“…Both the aetiology and pathogenesis of Hodgkin's disease are unresolved, but it is usually considered primarily a disease of the lympho-reticuloendothelial cells, sometimes with secondary stimulation of growth of other cell types such as fibroblasts (Wahl et al, 1978;Kaplan et al 1977). If, indeed, the isolated HD fibroblasts differ from normal fibroblasts as indicated by our study, 2 more possibilities arise.…”
Section: Discussionmentioning
confidence: 72%
“…Retroviruses have been isolated from several leukaemic patients by co-cultivation of tumour tissues with mammalian cell lines (Gallagher & Gallo, 1975;Panem et al, 1975;Smith et al, 1979;Gabelman et al, 1975;Kaplan et al, 1977). The best studied of these human virus isolates is HL23 virus (Gallagher & Gallo, 1975).…”
Section: Discussionmentioning
confidence: 99%